How to win at checkers (every time) [videorecording (DVD)] - Kim, Josh; Lapcharoensap, Rattawut; Rakkaen, Toni; Chutikul, Thira; Navarat, Arthur (Wolfe Video, 2016)
Both of his parents are dead, and now 11-year-old Oat's older (and only) brother must submit to Thailand's annual military draft lottery. Should he get drafted, there will be nobody left to care for Oat. Unable to convince his brother to take any extreme measures, young Oat takes matters into his own hands.